Mature tertiary lymphoid structures linked to HPV status and anti-PD-1 based chemoimmunotherapy response in head and neck squamous cell carcinoma - Lizao Zhang; Siqi Ren; Tianjun Lan; Ventin Marco; Niu Liu; Bin Wei; Yunsheng Chen; Jiaying Wu; Qunxing Li; Fan Wu; Peichia Lu; Jiahao Miao; et al. (OncoImmunology, 2025)
Mature tertiary lymphoid structures (TLSs) are immune aggregates associated with immune checkpoint blockade (ICB) responses in various cancers, yet their role in chemoimmunotherapy response in head and neck squamous cell carcinoma (HNSCC) remains unclear. By analyzing TCGA-HNSC transcriptomic data and pathology slides, we identified an immune subtype enriched in TLSs, predominantly in HPV-positive tumors, which correlated with favorable immunotherapy response. Single-cell and spatial transcriptomics further revealed distinct TLS compositions, with mature TLSs enriched in germinal center B cells, follicular helper T cells, and resident memory CD8 T cells, while immature TLSs contained FCRL4+ B cells and peripheral helper T cells. Multispectral immunohistochemistry, flow cytometry, and ELISA validated these findings. Notably, neoadjuvant chemoimmunotherapy promoted mature TLS formation. These results suggest that TLS maturity correlates with HPV status and response to anti-PD-1-based chemoimmunotherapy, providing insights for potential therapeutic strategies in HNSCC.